Atlas of transformation - Havránek, Vit; Baladrán, Zbyněk (Zurich : JRP/Ringier, 2010)
"Atlas of Transformation", with its almost 900 pages, is a sort of global guidebook of transformation processes. With structured entries, its goal is to create a tool for the intellectual grasping of the processes of social and political change in countries that call themselves "countries of transformation." Contains more than 200 'entries' and key terms of transformation. Several dozen authors from the whole world contributed to this book and also some influential period texts are republished here.
boek
Keywords: Art, East European -- 21st century; Art, Central European -- 21st century; Cultural geography -- Europe, Eastern; Cultural geography -- Europe, Central; Art and society -- Europe, Eastern; Art and society -- Europe, Central; Art -- Political aspects -- Europe, Eastern; Art -- Political aspects -- Europe, Central